Effect of Photoperiod on Chinese Kale (Brassica alboglabra) Sprouts Under White or Combined Red and Blue Light - Chen, Jiaxuan; Chen, Zeyuan; Li, Zunwen; Zhao, Yijiao; Chen, Xiaodong; Wang-Pruski, Gefu; Guo, Rongfang (Frontiers in Plant Science, 2021)
Abstract: To determine the response of Chinese kale (Brassica alboglabra) sprouts to photoperiods under different light sources, we used four photoperiods (0 h light/24 h dark, 8 h light/16 h dark, 12 h light/12 h dark, and 16 h light/8 h dark) to investigate their sprout growth and secondary metabolite glucosinolates (GS) accumulation under white or combined red-and-blue (RB) light sources. We found that the 16-h light condition under RB light produced plants with the greatest dry matter. Sprouts grown under 16-h RB light condition achieved greater length than those under white light. To investigate the role of RB light in plant growth and GS accumulation, we applied RB light sources with different RB ratios (0:10, 2:8, 5:5, 8:2, and 10:0) to cultivate sprouts. The results showed that significant differential accumulation of GS existed between sprouts grown under blue (RB, 0:10) and red (RB, 10:0) light; there was greater GS content under blue light. The underlying mechanism of differential GS content in sprouts under red or blue light condition was studied using RNA sequencing technique. Interestingly, abundant GS biosynthetic gene transcripts were observed in sprouts grown under red light compared with under blue light. The expression of β-glucosidase family homolog genes related to GS degradation differed under red and blue light conditions, among those TGG4 homolog was detected with higher expression under red light than with blue light. Taking into consideration, the lower GS accumulation in sprouts under red rather than blue light, we conclude that the degradation of GS may play a key role in sprouts GS homeostasis.